Winter monitoring of damaged bridges: learning from the December 2015 floods in Cumbria, UK. Issue 5 (15th May 2018) - Mathews, Richard; Hardman, Martin
Abstract : The December 2015 storms resulted in unprecedented damage to bridges in Northern England, UK. In Cumbria, the inspection of lower-priority structures was then delayed by continuing high water levels and the need to prioritise scarce diving resources to the repair works. Thus, full inspections were not completed until after the end of the summer river access period, leaving over 180 bridges that could not be repaired because rising river levels prevented safe access. This paper describes the risk-based strategy adopted to manage the monitoring and urgent repair of damaged bridges during the winter of 2016/2017. The strategy combined the engineering assessment of bridge condition and catchment-based river-level informatics to provide duty engineers with timely warning of river flows deemed likely to cause further risk, thus enabling them to call out inspection and maintenance engineers to assess the risks on-site and, where necessary, assure public safety by initiating bridge closures. The lessons learnt from the implementation of this strategy on this 10% sample of Cumbria's bridge stock will be used to inform the selection of measures for resilience against the effects of climate change and to develop county-wide emergency preparedness processes for all the highways network structures.